Implementation of Creative Thinking Skills in V Grade Students at SDN Kebonsari Kulon 1 Probolinggo - Firda Oktaviaji; Ludfi Arya Wardana; Faridahtul Jannah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The 21st century demands the mastery of creative thinking skills that are essential for every individual. At SDN Kebonsari Kulon 1 Probolinggo, grade V teachers have implemented creative learning strategies, such as the use of group presentation tasks to train students to face future difficulties. This study aimed to describe the implementation of creative thinking skills of grade V students, specifically related to four important aspects, namely fluency, flexibility, originality and detail. This analysis used a descriptive qualitative methodology, with research respondents including school leaders, grade V educators and students. The data collection strategies applied were interviews, observation, and documentation. The collected data were analyzed through the stages of collection, reduction, presentation, and conclusion drawing. The results of the analysis prove that the creative skills of grade V students have met the criteria based on four aspects. In the aspect of fluency, most students meet two of the three indicators, namely there are still students who feel reluctant to ask questions when they become an audience. In the aspect of flexibility, students were able to meet two of the three indicators, but some students were not able to classify ideas based on different criteria. All students met the indicators in the aspect of originality, as evidenced by their ability to find unique ideas in group discussions. In the aspect of detail, all indicators were met, as seen from the students' ability to explain in detail and coherently. In conclusion, the creative thinking skills of fifth grade students at SDN Kebonsari Kulon 1 Probolinggo are very good. However, there are still two indicators that have not been fully achieved, namely shyness to ask questions and difficulty in categorizing ideas based on different criteria. But overall, the implementation of creative thinking skills is very good.